2007
DOI: 10.1295/polymj.pj2006126
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Amphiphilic Polysilsesquioxane by Grafting of Block Copolymer of Acrylamide Monomers

Abstract: ABSTRACT:The polysilsesquioxane having dithiocarbamate groups was utilized for the graftation of N-isopropylacrylamide (NIPAM) and N,N-dimethylacrylamide (DMAA) under thermal polymerization conditions. The controlled graft polymerization through RAFT process proceeded effectively to give several kinds of block copolymer of NIPAM and DMAA without formation of gel product, in which the sequence and the number of the monomer units were changed. The introduction of the block copolymers provided an amphiphilic prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
23
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…[10][11][12][13][14][15][16] In the previous works, we also have investigated concerning the graft polymerizations from polysilsesquioxane backbone, which intended to develop the new multi-functional hybrid materials. [17][18][19][20][21] As an example of such graftings, the introduction of block copolymer of N,N-dimethylacrylamide (DMAA) and N-isopropylacrylamide (NIPAM) by the living polymerization technique, reversible addition-fragmentation chain transfer (RAFT) process, was reported. 21 In the graft polymerization, the PSQ having chloromethylphenyl groups (CPPSQ) was prepared from the corresponding trimethoxysilane and, then, N,N-dimethyldithiocarbamate (DTC) group was introduced as a chain transfer specie for RAFT process.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…[10][11][12][13][14][15][16] In the previous works, we also have investigated concerning the graft polymerizations from polysilsesquioxane backbone, which intended to develop the new multi-functional hybrid materials. [17][18][19][20][21] As an example of such graftings, the introduction of block copolymer of N,N-dimethylacrylamide (DMAA) and N-isopropylacrylamide (NIPAM) by the living polymerization technique, reversible addition-fragmentation chain transfer (RAFT) process, was reported. 21 In the graft polymerization, the PSQ having chloromethylphenyl groups (CPPSQ) was prepared from the corresponding trimethoxysilane and, then, N,N-dimethyldithiocarbamate (DTC) group was introduced as a chain transfer specie for RAFT process.…”
mentioning
confidence: 99%
“…[17][18][19][20][21] As an example of such graftings, the introduction of block copolymer of N,N-dimethylacrylamide (DMAA) and N-isopropylacrylamide (NIPAM) by the living polymerization technique, reversible addition-fragmentation chain transfer (RAFT) process, was reported. 21 In the graft polymerization, the PSQ having chloromethylphenyl groups (CPPSQ) was prepared from the corresponding trimethoxysilane and, then, N,N-dimethyldithiocarbamate (DTC) group was introduced as a chain transfer specie for RAFT process.The previous results demonstrated that the block copolymer grafted PSQs showed an expected amphiphilic property, where the solubility in water was influenced by the sequence and number of the monomer units in the grafted chain. 21 Namely, when the more hydrophilic poly(DMAA) was grafted from the polysilsesquioxane backbone at first and poly(NIPAM) was grafted after poly(DMAA) component [poly(DMAA)-blockpoly(NIPAM)], hydrophilic property of the corresponding PSQ was effectively improved.…”
mentioning
confidence: 99%
See 3 more Smart Citations